Matrix metalloproteinase‐10 expression is induced during hepatic injury and plays a fundamental role in liver tissue repair. (16th October 2013) - Garcia‐Irigoyen, Oihane; Carotti, Simone; Latasa, Maria U.; Uriarte, Iker; Fernández‐Barrena, Maite G.; Elizalde, Maria; Urtasun, Raquel; Vespasiani‐Gentilucci, Umberto; Morini, Sergio; Banales, Jesús M.; Parks, William C.; Rodriguez, Jose A.; et al.
Abstract Background & Aims Upon tissue injury, the liver mounts a potent reparative and regenerative response. A role for proteases, including serine and matrix metalloproteinases (MMPs), in this process is increasingly recognized. We have evaluated the expression and function of MMP10 (stromelysin‐2) in liver wound healing and regeneration. Methods The hepatic expression of MMP10 was examined in two murine models: liver regeneration after two‐thirds partial hepatectomy (PH) and bile duct ligation (BDL). MMP10 was detected in liver tissues by qPCR, western blotting and immunohistochemistry. The effect of growth factors and toll‐like receptor 4 (TLR4) agonists on MMP10 expression was studied in cultured parenchymal and biliary epithelial cells and macrophages respectively. The role of MMP10 was evaluated by comparing the response of Mmp10+/+ and Mmp10−/− mice to PH and BDL. The intrahepatic turnover of the extracellular matrix proteins fibrin (ogen) and fibronectin was examined. Results MMP10 mRNA was readily induced after PH and BDL. MMP10 protein was detected in hepatocytes, cholangiocytes and macrophages. In cultured liver epithelial cells, MMP10 expression was additively induced by transforming growth factor‐β and epidermal growth factor receptor ligands. TLR4 ligands also stimulated MMP10 expression in macrophages. Lack of MMP10 resulted in increased liver injury upon PH and BDL. Resolution of necrotic areas was impaired, and Mmp10−/− mice showed increased fibrogenesis and defective turnover of fibrin (ogen) and fibronectin. Conclusions MMP10 expression is induced during mouse liver injury and participates in the hepatic wound healing response. The profibrinolytic activity of MMP10 may be essential in this novel hepatoprotective role.